Strychnos potatorum: Phytochemical and pharmacological review - Yadav, Kavita N.; Kadam, Prasad V.; Patel, Jigna A.; Patil, Manohar J. (Pharmacognosy Reviews)
In traditional system of medicine, the seeds of Strychnos potatorum Linn. (family: Loganiaceae) are used in the treatment of gonorrhea, leukorrhea leukeorrhea, gastropathy, bronchitis, chronic diarrhea, dysentery, renal and vesicle calculi, diabetes, conjunctivitis, scleritis, ulcers and other eye disease. An attempt has been made to highlight this medicinal seeds through phytochemical and pharmacological study. The present review deals with the phytochemical and pharmacological screening of therapeutic importance from Strychnos potatorum L., an important medicinal plant. This study includes the collective information of different medicinal uses of Strychnos potatorum. The generated data has provided the basis for its wide use as the therapeutant both in the traditional and folk medicines.
Keywords: Medicinal plant; phytochemical; Strychnos potatorum